The Evaluation Of Jayapura City Government Financial Performance - Tanan, Christina Irwati; Kakisina, Jonathan (STIE PGRI Dewantara Jombang, 2020)
This study aimed to determine the results of measuring financial performance to evaluate financial performance in order to improve financial performance which can improve the financial performance of the Jayapura City Government. This type of research was descriptive quantitative. The object of this research was the financial statements of Jayapura City in 2011 - 2017. The results showed that: 1) Local Revenue of Jayapura City in 2011 - 2017 had increased, 2) The dependence of the Jayapura City Government on the Central Government was decreasing, 3) the self-reliance ratio was still very low, 4) the effectiveness ratio> 100% or very effective, 5) the efficiency ratio was included in the very efficient